The Employment Effect of Inward FDI in China: What Do We Learn from the History? - Hao Wang; Yuemei Ji; Qi Luo (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This study investigates the long-term influence of colonial legacy on the nexus between inward foreign direct investment (FDI) and labor market. We construct a panel dataset containing 285 Chinese cities 2011 to 2017 along with detailed information about Chinese modern history during 1842-1955). Our results show that the inward FDI has a positive effect on employment and such an effect is more pronounced in the regions with colonial influence than their counterparts. Further, we find that the experience of Western colonization strengthens the positive effect of inward FDI on employment whereas the experience of Japanese colonization weakens or even overturns this positive effect. These findings are robust to controlling for the endogeneity between inward FDI and employment as well as employing alternative measures for the colonization.
Keywords: N01; F21; J23; 330; colonial legacy; foreign direct investment; employment; Chinese modern history